Idiopathic Dilated Cardiomyopathy in a 14-Year-Old Girl Presenting with Acute Biventricular Heart Failure at Sunyani Teaching Hospital in Ghana: A Case Report - Elisha, Awuah; Alexander, Egote Kofi; Edward, Bediako Mensah; Henry, Andoh K.; Banabas, Kpankyaano; Frank, Amo-Kodieh; Michael, Opare; Maxwell, Gershin Peter (British Journal of Healthcare and Medical Research, 2025)
Dilated cardiomyopathy (DCM) is a rare but life-threatening condition in adolescents, often presenting with vague respiratory symptoms that delay diagnosis, especially in low-resource settings. We report the case of a 14-year-old girl who presented with acute biventricular heart failure after a three-year history of intermittent dyspnea, orthopnea, and lower limb swelling. Initial clinical suspicion at peripheral facilities was low due to nonspecific symptoms and the absence of comorbidities. Echocardiography revealed severe biventricular dysfunction, an ejection fraction of 18%, significant chamber enlargement, severe functional mitral regurgitation and no congenital heart defect was detected. Electrocardiography showed sinus tachycardia with left atrial enlargement. The patient responded well to guideline-directed medical therapy including diuretics, ACE inhibitors, beta-blockers, and aldosterone antagonists. This case illustrates the diagnostic challenge of recognizing idiopathic DCM in adolescents, particularly in sub-Saharan Africa where cardiac imaging may be limited. It also reinforces the importance of early echocardiographic evaluation in patients with unexplained respiratory symptoms. Early recognition and standard heart failure therapy can significantly improve outcomes in paediatric DCM, even in cases presenting late with advanced dysfunction.